2018
DOI: 10.1159/000491656
|View full text |Cite
|
Sign up to set email alerts
|

CDK13 RNA Over-Editing Mediated by ADAR1 Associates with Poor Prognosis of Hepatocellular Carcinoma Patients

Abstract: Background/Aims: Aberrant RNA editing, mediated by adenosine deaminases acting on RNA (ADAR), serves as a post-transcriptional event participating in tumorigenesis and prognosis. However, the RNA editing profiles during HCC progression and their clinical correlations remain unclear. Methods: Multiple tissue samples were collected from an advanced HCC patient. RNA-seq was performed to obtain the RNA editing profiles for each sample. Two RNA editing sites from CDK13 were further validated in 60 HCC patients; and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 30 publications
4
18
0
Order By: Relevance
“…Considering the important overall impact of RNA editing on cancer [15, 2628], we asked whether inosinome might correlate with patients’ clinical parameters such as OS, age at diagnosis, or the Karnofsky Performance Score (KPS).…”
Section: Resultsmentioning
confidence: 99%
“…Considering the important overall impact of RNA editing on cancer [15, 2628], we asked whether inosinome might correlate with patients’ clinical parameters such as OS, age at diagnosis, or the Karnofsky Performance Score (KPS).…”
Section: Resultsmentioning
confidence: 99%
“…CDK13 had been paid close attention in the children with certain types of congenital heart defects, and the heterozygous missense mutations of CDK13 would impair magnesium ion binding to ATP in these pediatric sufferers, yet no further studies were performed (Bostwick et al, 2017;Uehara et al, 2018;Hamilton and Suri, 2019;Novakova et al, 2019). The role of CDK13 in cancers, such as ovarian cancer and hepatocellular carcinoma, has been focused on since 2018; however, no underlining mechanism has been reported (Dong et al, 2018;Zeng et al, 2018;Wang et al, 2019). TCGA database showed that CDK13 is amplified in different categories of cancer, indicating it could contribute to the tumorigenesis and development of cancer in humans.…”
Section: Introductionmentioning
confidence: 99%
“…In this series of experiments, we chose three different RNAs as substrates, Cdk13 , NICN1 , and NEIL1 . Cdk13 is canonically edited by ADAR1, resulting in Q103R amino acid substitution (Dong et al., 2018; Maas et al., 2011; Sakurai et al., 2014). More than 30 adenosine residues within the inverted repeat Alu sequence in a 3’ untranslated region (3’ UTR) of the NICN1 RNA have reported to be randomly edited (Bazak et al., 2014; Chen et al., 2008; Nishikura, 2016).…”
Section: Resultsmentioning
confidence: 99%